PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN PENGUASAAN KONSEP IPA PADA MATERI TEKANAN ZAT DI MTs NUR MA'ARIF KOTA JAMBI - Juvi, Padmi Adika; Sukarno, Sukarno; Purnama, Boby Yasman (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2025)
Observation Results Show that student learning outcomes in science lessons on substance pressure material are still low. Many teachers use conventional methods. Students only listen and take notes. Therefore, the use of appropriate and varied learning models is expected to help students in lessons. The purpose of this study was to determine the extent to which the Problem Based Learning (PBL) learning model influences critical thinking skills and mastery of Science concepts on substance pressure material for class VIII C students, odd semester at MTs Nur Ma'arif, Jambi City, 2024/2025 academic year. Sampling was carried out using the Cluster Random Sapling technique. The study population was all class VIII students of MTs Nur Ma'arif, Jambi City. The sample used was class VIII C students, The variables in this study were critical thinking and student concept mastery in science learning on substance pressure material, design (one group pretest-posttest) taking through pretest before treatment and posttest after treatment was given based on the comparison, there was an increase as evidenced by the Ngain test obtaining a value (0) then it was stated that there was a high increase. and the